The Impossible Trinity: Inflation Targeting, Exchange Rate Management and Open Capital Accounts in Emerging Economies. Issue 3 (May 2017) - Kaltenbrunner, Annina; Painceira, Juan Pablo
ABSTRACT: This article contributes to the debate on macroeconomic management and capital account regulations in developing and emerging countries (DECs). It argues that the recommendation by neoclassical economists and international financial institutions (IFIs) to combine an inflation‐targeting regime with exchange rate management, whilst maintaining open capital accounts, is not only impossible but also potentially counterproductive. The article draws on extensive semi‐structured interviews with currency traders in Brazil and London to show that this is due to the particular way such a regime shapes central bank interventions in the money and foreign exchange markets and the destabilizing way these interventions interact with financial market expectations. The interview results also demonstrate that the guidelines issued by IFIs actually undermine, rather than aid, DEC central banks' initial attempts to manage excessive exchange rate movements. These results support the long‐standing argument by heterodox economists and critical international political economists that DECs need to make the exchange rate an explicit instrument and goal of their macroeconomic policy and complement it with comprehensive capital account regulations to reduce the destabilizing impact of international capital flows. The interview results also give some concrete suggestions on how to achieve this.